Facilitating Trade through Rules of Origin: A Consideration of the African Continental Free Trade Area - Okoroma, Blessing Ijeoma (University of Calgary, 2024)
Rules of origin play a pivotal role in free trade agreements. Apart from serving as a tool to distinguish goods by determining the nationality of a product, rules of origin have the capacity to increase trade relations or deter it. Of course, it is the hope of any viable state to increase profitable trading relations, and if rules of origin can help with that, it becomes expedient to fully understand how these rules of origin operate. In Africa, we see rules of origin being implemented amongst the Regional Economic Communities (RECs), but this has come with many struggles. In fact, low intra-African trade can be narrowed down to complex rules of origin regimes deployed in regional agreements in Africa. As of date, the major RECs have each implemented different rules of origin, leading to the co-existence of conflicting rules of origin across Africa. This non-uniformity in the rules of origin regimes in Africa has resulted in low continental trade in Africa. As such, these RECs have not yielded the expected increase in intra-African trade. With the creation of the African Continental Free Trade Area (AfCFTA), which currently doubles as the latest and largest FTA in Africa, it is expected that better rules of origin will be deployed to mitigate the existing intra-African trade deficits. This thesis thus deploys a doctrinal approach in determining whether AfCFTA’s rules of origin are positioned to achieve greater intra-African trade. Consequently, this thesis uncovers some lapses in AfCFTA’s rules of origin and calls for harmonization of all the rules of origin in Africa and recommends a possible amendment to Article 19 of the Agreement establishing AfCFTA to accommodate the intended harmonization.
Keywords: African Continental Free Trade Area; Free Trade Area; Rules of Origin

The use of blockchain technology in international commercial transactions, with specific reference to secured payments in international contracts of sale - Muza, Chido Teclar Mitchel (University of Johannesburg, 2022)
Please refer to full text to view abstract.
Keywords: Blockchains (Databases); Commercial law; Electronic funds transfers; Export sales contracts.; Foreign trade regulation

Unification of international sales law in the SADC region : the role and significance of the CISG - Simelane, Mbalenhle Pearl (University of Johannesburg, 2019)
The United Nations Commission on International Trade Law (UNCITRAL) is one of the most prominent legal bodies in international commerce. In 1980, the final draft of the United Nations Convention on Contracts for the International Sale of Goods (CISG or the Convention) was approved by the United Nations (UN) General Assembly and came into operation on 1 January 1988. Generally, the diversity of laws is an impediment to international and regional trade. Traders are discouraged from entering into international sales contracts due to the dissimilarities of legal systems. However, the CISG seeks to unify laws relating to the international sale of goods, whilst codifying the existing rules of international trade. The main objectives of the Southern African Development Community (SADC) are to achieve development and economic growth through regional integration.1 The legal integration and unification of sales law has a significant role to play in regional integration. Hence, SADC would do away with difficulties that affect interregional and intra-regional trade by impeding economic growth by making use of widely accepted trade laws, such as the Convention. International trade promotes both economic development and social upliftment. Moreover, democracy, political stability and human rights must be respected to foster sustainable economic growth and development in Southern Africa. 2 With advantages such as accessibility, flexibility, indorsing party autonomy, simplicity, and uniform interpretation, the paper revisits the call for the unification of laws on the sale of goods in SADC and considers the role and significance of the CISG in the region. LL.M. (Commercial Law)
Keywords: Commercial law; International economic integration; International trade Law; International unification

The role of the SADC Protocol on Trade in Services in regional integration - Swanepoel, L. B. (North-West University, 2018)
Trade in Services can be described as a transaction between a supplier and a consumer without any physical movement of goods across international borders. This, in itself, presents major economic growth possibilities in both regional and multilateral terms. Regional trade agreements, if drafted to suit the specific region's strengths, can promote Trade in Services and establish regional integration. The fact that Trade in Services and regional integration, throughout the Southern African Development Community (SADC) specifically, is moving forward at such a slow pace is due to the lack of political ambition and policy makers failing to emphasise the establishment of trade specific regulatory coherence among member states. Given policy’s impact on Trade in Services, regional trade agreements must be designed to address new and emerging issues that, not only haven't been taken up in previous trade agreements, but which is also region specific and focused enough to build on new standards found in other new trade agreements that will boost regional integration. SADC countries are still in process of establishing a regional services market and, as it currently stands, major development possibilities still exist. This study compares the Trans-Pacific Partnership (TPP) with SADC’s Protocol on Trade in Services (PTIS), with the goal to determine the principles that are necessary to establish a regional market for the integration of Trade in Services. It was found that the PTIS lacks such principles and that integration of services throughout the SADC region is highly unlikely if set forth in its current direction. The finding was that the establishment of regional integration of Trade in Services throughout SADC will have to start with regulatory coherence among its members.
Boloka Institutional Repository https://repository.nwu.ac.za/handle/10394/31341
Keywords: Modes of trade; Regional integration; Regulatory coherence; Trade in Services

Choice of law in international commercial contracts : a comparative study of Private International Law in Ghana and South Africa - Kwame, Essah (University of Johannesburg, 2018)

Modification of choice of law in the BRICS countries : the role of Article 2(3) of the Hague Principles on choice of law in international commercial contracts - Ndlovu, Docus Sanele (University of Johannesburg, 2018)
Each member state of the BRICS countries is different about the modalities and limitations of party autonomy in their field of Private International law. The principle of party autonomy allows parties to choose the law applicable to their contract and is meant to respect the choice of contracting parties. Since laws are not absolute, they need to change to the needs of a changing society. This can generate a problem in instances where contracting parties have already chosen a choice of law to govern their contract. The question is then whether the governing law of a contract that was previously chosen by the parties can be changed after that contract has been concluded. The scope of party autonomy extends to permitting parties to modify their chosen law in instances where it is necessary to do so, subject to limitations of a specific legal system and principles of conflict of laws. However, the legal rules of each BRICS countries differ in permitting parties to modify the chosen law. This minor dissertation analyses whether the principle of party autonomy is recognised in each member state of the BRICS countries and whether it extends to allow for modification of choice of law. It further asserts that the BRICS countries could plausibly refer to the rules and recommendations of Article 2(3) of the Hague Principles on Choice of Law in International Commercial Contracts to advance the wide acceptance of modification of choice of law. LL.M. (International Commercial Law)

A tranferência do risco no contrato de venda internacional de mercadorias em trânsito no âmbito da Convenção de Viena de 1980 - Damião, Ana Raquel Modesto (Universidade Nova de Lisboa, 2017)
International trade has had an increasing impact on the national economies of states. For this reason, some international institutions have sought to standardise rules on the international sale of goods. The Convention, which stands out from these rules, is the United Nations Convention on Contracts for the International Sale of Goods, opened for signature in Vienna on 11th April, 1980, known as the Vienna Convention (CISG). The transfer of risk is one of the most sensitive issues in international trade. Therefore, it would seem apt to observe the legal regime of the transfer of risk contained in the various provisions of this international instrument. To understand the rules of the transfer of risk, it is necessary to observe the notion of contract for the international sale and the obligations of the parties involved in the international contract. In addition, it should be noted that, in most situations, the contract for the international sale is related to the transport of goods. With this framework, the study of this essay focuses on the analysis of article 68 of the Vienna Convention. So, this dissertation deals with the question of determining the exact moment of the transfer of risk in the contract of international sale of goods in transit under the Vienna Convention. O comércio internacional tem tido cada vez mais impacto nas economias nacionais dos Estados. Por esse motivo, algumas organizações internacionais têm procurado uniformizar as regras relativas à compra e venda internacional de mercadorias. A Convenção, que se destaca dessas regras, é a Convenção das Nações Unidas sobre os Contratos de Compra e Venda Internacional de Mercadorias, aberta à assinatura em Viena a 11 de abril de 1980, conhecida como Convenção de Viena. A transferência do risco apresenta-se como uma das temáticas mais delicadas do comércio internacional. Portanto, afigura-se como útil a observação do regime jurídico da transferência do risco contido nas diversas disposições deste instrumento internacional. Para compreender as regras da transferência do risco, é necessário observar a noção de contrato de compra e venda internacional e as obrigações das partes do contrato internacional. Além disso, há que perceber que, na generalidade das situações, o contrato de compra e venda internacional está relacionado com o transporte de mercadorias. Com este enquadramento, o estudo deste trabalho centra-se na análise do artigo 68.º da Convenção de Viena. Assim, a presente dissertação debruça-se sobre a questão de determinar qual é o momento exato da transferência do risco no contrato de compra e venda internacional de mercadorias em trânsito no âmbito da Convenção de Viena.
Keywords: Convenção de Viena; Goods in transit; International sale; Mercadorias em trânsito; Transfer of risk; Transferência do risco; Venda internacional; Vienna Convention

Formation of Contract for the International Sales of Goods - Saleem, Saman Othman (Near East University, 2016)
The Convention for the International Sale of Goods called the Vienna Conference 1980 is an astute international statute that regulates the sale of goods globally. It has been ratified by about 83 countries of the world and countries that have not ratified it have at a point or the other made reference to it. Major economic players apart from England have ratified and have their courts pronounce on the CISG. The Convention provides for the well known elements of contract and also allows for the usage of standard user terms, for example, general terms known or related to certain goods. It is imperial to state that there are also certain regional statutes that are similar to the CISG although with varying differences. It is important to also mention that the CISG also has its lacunae and defects such as allowance for exemption, contents and so on. The CISG has been pronounced upon by courts across the world and has been seen to be highly justiciable.
Keywords: CISG; Convention; English Law; Iraq; United Nations

Choice of the UNIDROIT Principles of international commercial contracts - Meer, Tiana Van der (University of Johannesburg, 2015)
LL.M. (International Commercial Law) The principle of party autonomy is a fundamental characteristic of private international law. The contracting parties’ freedom of choice regarding the law governing their contract is one which optimises the fundamental principle of party autonomy. It is generally accepted that a choice of a governing law by the parties should be respected by adjudicating bodies such as domestic courts and arbitral tribunals. It would often benefit contracting parties to choose a neutral legal system so that there will be a “fair playing field” in case a dispute arises between them. However, some domestic legal systems and regional, supranational and international commercial instruments limit the choice of law to that of a recognised domestic legal system. Accordingly, choosing the UNIDROIT Principles on International Commercial Contracts as governing law will, in most cases, not be a viable option for the parties concerned. Such a limitation on the choice of a governing law does not promote the fundamental principle of party autonomy, which is characteristic of private international law. Parties to an international commercial contract should be able to choose a non-state system of law to govern their contract. The UNIDROIT Principles of International Commercial Contracts provide a comprehensive, complete and easily obtainable system of law compiled by legal experts in the various fields which form part of international commercial law. It follows a via media system of law with regards to Civil Law and Common Law legal systems. This paper will discuss the principle of party autonomy, as well as the possibility of a choice of non-state law, in particular the UNIDROIT Principles of International Commercial Contracts, as the law governing an international commercial contract. The choice of law will be discussed with reference to the position taken in domestic courts as well as that in international arbitration. To review the impact and success of the UNIDROIT Principles in the realm of international commercial contracting, various international commercial instruments will be discussed.

La formation du contrat électronique international : le formalisme au regard de la convention CNUDCI 2005 - Mehdaoui, Kamel (Université du Québec à Montréal, 2010)
Les progrès spectaculaires et rapides dans les domaines technologiques, essentiellement la technologie de l'information, recèlent des enjeux juridiques à la mesure de ces phénomènes. En effet, les communications se transmettent plus loin et plus vite que jamais. On conclut des marchés, on mène des transactions et on prend des décisions dans des délais qui auraient tout simplement semblé inconcevable dans le passé. La vente internationale demeure sans doute le principal instrument du commerce international. Cette importance se manifeste par l'uniformité juridique essentiellement à travers les conventions internationales. Une nouvelle situation de relation juridique, entre le contrat de vente internationale de marchandises et le commerce électronique, se concrétise en réalité par la conclusion des contrats de vente par l'intermédiaire de réseaux de télécommunication essentiellement l'Internet. Néanmoins, la matière juridique, en évolution constante dans un environnement international, prend sa source dans une multitude de conventions. Dans ce cadre général, nous analyserons le contrat électronique international.
Keywords: Commerce international; Commerce électronique; Contrat électronique; Formalisme contractuel; Signature électronique

Le dumping à la lumière des accords du GATT et de la Loi des mesures spéciales d'importation - Leduc, François (Université de Montréal, 1990)
Keywords: Accord général; Commerce; Tarifs douaniers

Le règlement des différends en matière de dumping et de subventionnement à la lumière de l'Accord de libre-échange canado-américain - Saucier, Emmanuelle (Université de Montréal, 1990)
Keywords: Accord de libre-échange; Canada; Dumping (International trade); Etats-Unis; Règlement des différends